2019
DOI: 10.1038/s41419-018-1296-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of caspase-2 deficient EμMyc and Th-MYCN mouse tumors identifies distinct putative roles for caspase-2 in neuronal differentiation and immune signaling

Abstract: Caspase-2 is a highly conserved cysteine protease with roles in apoptosis and tumor suppression. Our recent findings have also demonstrated that the tumor suppression function of caspase-2 is context specific. In particular, while caspase-2 deficiency augments lymphoma development in the EμMyc mouse model, it leads to delayed neuroblastoma development in Th-MYCN mice. However, it is unclear how caspase-2 mediates these differential outcomes. Here we utilized RNA sequencing to define the transcriptomic changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
2
5
0
Order By: Relevance
“…The RNA-sequencing data identified differential expression of oxidative stress-related genes including SESN2, HMOX1, SLC7A11 in mut-p53 cancer cells without caspase-2 under basal conditions. These observations are consistent with previous studies implicating the association of caspase-2 loss with transcriptional regulation of genes involved in tumorigenesis and redox signaling [ 4 , 14 ]. Collectively, these studies imply that caspase-2 loss supports a favorable environment for ferroptosis and does not simply act by enhancing the kinetics of erastin effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The RNA-sequencing data identified differential expression of oxidative stress-related genes including SESN2, HMOX1, SLC7A11 in mut-p53 cancer cells without caspase-2 under basal conditions. These observations are consistent with previous studies implicating the association of caspase-2 loss with transcriptional regulation of genes involved in tumorigenesis and redox signaling [ 4 , 14 ]. Collectively, these studies imply that caspase-2 loss supports a favorable environment for ferroptosis and does not simply act by enhancing the kinetics of erastin effect.…”
Section: Discussionsupporting
confidence: 93%
“…Caspase-2 has previously been shown to influence transcriptome changes driven by oncogene activation and tumor suppressor loss in a context-specific manner [ 4 ]. To identify the transcriptomic differences and gene enrichment pathways affected by CASP2 deficiency in mut-p53 cancer cells, we carried out RNA sequencing in H1299p53 R273H cancer cells with acute loss and knockout of caspase-2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The RNA sequencing data identified differential expression of oxidative stress related genes including SESN2, HMOX1, SLC7A11 in mut-p53 cancer cells without caspase-2 under basal conditions. These observations are consistent with previous studies implicating association of caspase-2 loss with transcriptional regulation of genes involved in tumorigenesis and redox signaling (4,14). Collectively, these studies imply that caspase-2 loss supports a favourable environment for ferroptosis and does not simply act by enhancing kinetics of erastin effect.…”
Section: Discussionsupporting
confidence: 92%
“…Caspase-2 is the most conserved member of the caspase family and is well studied for its role as a tumor suppressor under conditions of oncogenic or replicative stress. Previous in vivo studies have established that caspase-2 deficient (Casp2 −/− ) mice do not develop spontaneous tumors (1) but have enhanced susceptibility to tumorigenesis promoted by activation of oncogenes (K-Ras, EμMyc and MMTV/c-neu) (2)(3)(4)(5) or loss of a critical tumor suppressor gene (ATM) (6). Furthermore, studies from human cancers have reported that the CASP2 gene located on Ch7q is frequently deleted in haematological malignancies (7).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this correlation was observed in neuroblastoma patients with nonamplified MYCN 96 . The tissue- and context-specific tumor suppressor function of caspase-2 was also apparent in the distinct transcription profiles of caspase-2-deficient Eμ-Myc and TH -MYCN mouse tumors 97 .…”
Section: Caspase-2 As a Tumor Suppressormentioning
confidence: 90%